2013
DOI: 10.1096/fj.13-236828
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' tumor 1 (Wt1) regulates pleural mesothelial cell plasticity and transition into myofibroblasts in idiopathic pulmonary fibrosis

Abstract: Pleural mesothelial cells (PMCs), which are derived from the mesoderm, exhibit an extraordinary capacity to undergo phenotypic changes during development and disease. PMC transformation and trafficking has a newly defined role in idiopathic pulmonary fibrosis (IPF); however, the contribution of Wilms' tumor 1 (Wt1)-positive PMCs to the generation of pathognomonic myofibroblasts remains unclear. PMCs were obtained from IPF lung explants and healthy donor lungs that were not used for transplantation. Short hairp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 51 publications
(64 reference statements)
5
75
1
Order By: Relevance
“…Interestingly, a similar conversion of MCs was recently reported in fibrosis of the adult liver or lung. 12,13 In the mouse liver, MCs express WT1, cytokeratin 8 (KRT8), and vimentin (VIM) but not E-cadherin (CDH1) and a-smooth muscle actin (ACTA2). 12 On liver injury, Wt1 þ MCs give rise to hepatic stellate cells or ACTA2 þ myofibroblasts, depending on causes.…”
mentioning
confidence: 99%
“…Interestingly, a similar conversion of MCs was recently reported in fibrosis of the adult liver or lung. 12,13 In the mouse liver, MCs express WT1, cytokeratin 8 (KRT8), and vimentin (VIM) but not E-cadherin (CDH1) and a-smooth muscle actin (ACTA2). 12 On liver injury, Wt1 þ MCs give rise to hepatic stellate cells or ACTA2 þ myofibroblasts, depending on causes.…”
mentioning
confidence: 99%
“…Among the proposed sources has been the mesothelial lining of the lung (3). The mesothelium is a polarized epithelial sheet that covers the surface of most visceral organs and is required for their normal development.…”
mentioning
confidence: 99%
“…These cells, like other mesothelial cells, express the transcription factor, Wilms' tumor 1 (Wt1), and Wt1-driven expression of constitutive Cre or inducible CreERT2 alleles has been used to trace the fate of PMCs during lung development, postnatal lung homeostasis, and lung disease, with conflicting results (3,(9)(10)(11). During lung development, one study using a constitutive Wt1-Cre transgene reported that PMCs contribute to vascular SMCs (11).…”
mentioning
confidence: 99%
“…Expression of the lung mesothelial marker WT1 has been observed in lung fibrotic lesions, suggesting that mesothelial cells or their differentiated progeny may contribute to lesion formation (Mubarak Karki et al, 2014). Mesothelial contribution to fibrosis has also been demonstrated in the liver, where the lineage-traced mesothelium invades into the submesothelial region and differentiates into fibroblasts following chemical injury (Asahina et al, 2011;Li et al, 2013).…”
Section: Aberrant Expression Of Tbx15/18 In Ezh2 Mesoderm-ko Lungsmentioning
confidence: 99%
“…Mesothelial cells differentiate into fibroblasts upon exposure to Tgfβ, a pro-fibrotic signaling molecule, which is upregulated in IPF lungs (Batra and Antony, 2015). Additionally, a mouse model of fibrosis by intratracheal Tgfβ1 instillation induces expression of the mesothelial-specific transcription factor Wilms tumor 1 (WT1) in the lung parenchyma (Karki et al, 2014). These data suggest that the mesothelium and mesothelial-derived cells might reactivate their developmental plasticity during lung injury and repair processes, and contribute to inappropriate fibrosis.…”
Section: Introductionmentioning
confidence: 97%